Land-Use Changes and the Effects of Oil Palm Expansion on a Peatland in Southern Thailand - Srisunthon, Prapawadee; Chawchai, Sakonvan (Frontiers in Earth Science, 2020)
Tropical peatlands are one of the largest reservoirs of terrestrial organic carbon. However, present-day tropical peat swamp forests are under threat by anthropogenic disturbances and have already been widely degraded. Anthropogenic pressures on peatland ecosystems have resulted in ecological and biogeochemical changes and the release of carbon to the atmosphere. In Southeast Asia, the conversion of peatlands to oil palm plantations has accelerated significantly during the last 2 decades. This research analyzed direct and indirect land-use changes (DLUC and ILUC) that have been associated with oil palm expansion and anthropogenic impacts in the Princess Sirindhorn Wildlife Sanctuary (PSWS), Narathiwat, southern Thailand. Our analysis is based on land-use and land-cover data of the Land Development of Thailand from two different periods: 2000–2009 and 2009–2016. For the purpose of comparison, the data were reclassified into 12 types of land use: oil palm, para rubber, paddy field, abandoned paddy field, orchard, other agriculture lands, wetlands and peatlands, mangrove, evergreen forest, water area, build-up area, and unused area. In addition, the area of net change due to DLUC and ILUC was calculated, and carbon stock changes were estimated from above- and below-ground biomass and soil organic carbon. The results show that the total oil palm plantation area has increased from 0.04% in 2000 to 6.84% in 2016, because of a Thai government policy promoting the use of biodiesel and increasing capacity of palm oil production in 2005. Paddy field, evergreen forest, wetlands, and peatlands were the main areas being replaced. The clearance of natural forest greatly increased in the period of 2000–2009. The ILUC indicates that the expansion of oil palm plantations invades other croplands (paddy field, para rubber, and orchard). The results demonstrate that the conversion of natural landscapes (evergreen forest, mangrove, wetlands, and peatlands) to oil palm plantations at Princess Sirindhorn Wildlife Sanctuary area had a negative effect, with carbon stock changes of 4 million Mg C during 2000–2016 (0.25 million Mg C/year). Given the significance of carbon stock changes arising from land-use changes, this research highlights the need for sustainable land-use management and long-term monitoring.